2009
DOI: 10.1111/j.1399-5618.2008.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of increased amygdala activation to positive affective stimuli in mania

Abstract: Objectives: The present study in hypomanic and manic patients explored how amygdala responses to affective stimuli depend on the valence of the stimuli presented. Methods:We compared 10 patients with 10 matched healthy control subjects. We measured blood oxygen level-dependent (BOLD) responses in the amygdala while subjects passively viewed photographs taken from the International Affective Picture System. After the fMRI session, subjects saw the pictures again and subjectively rated the emotional valence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 39 publications
7
39
0
Order By: Relevance
“…This finding is consistent with the increased perception of BD to attentional allocation of negative rather than to positive emotional cues [16]. Although some studies in non-euthymic BD (manic) have shown positive bias [55], others have demonstrated attentional biases toward negative valence stimuli in depressed BD patients employing non-facial emotion processing tasks [56]. Furthermore, enhanced recognition of negative facial expressions has been reported in euthymic BD [7], [57].…”
Section: Discussionsupporting
confidence: 74%
“…This finding is consistent with the increased perception of BD to attentional allocation of negative rather than to positive emotional cues [16]. Although some studies in non-euthymic BD (manic) have shown positive bias [55], others have demonstrated attentional biases toward negative valence stimuli in depressed BD patients employing non-facial emotion processing tasks [56]. Furthermore, enhanced recognition of negative facial expressions has been reported in euthymic BD [7], [57].…”
Section: Discussionsupporting
confidence: 74%
“…We predicted that bipolar subjects would exhibit abnormal activation within the ventrolateral prefrontal-amygdala emotional pathway, including decreased ventrolateral prefrontal activation consistent with prior studies and a model of decreased prefrontal modulation of limbic brain in mania (3, 1014). To test this prediction, we performed a region of interest (ROI) analysis based on this pathway.…”
supporting
confidence: 69%
“…During fMRI participants viewed standardized photographs taken from the International Affective Picture System (IAPS) [32] as previously described [38], [39]. The IAPS is an established stimulus set to elicit emotional responses.…”
Section: Methodsmentioning
confidence: 99%